Perkembangan Teledermoskopi di Indonesia: Tinjauan Perspektif Hukum Kesehatan - Reginata, Gabriela; Noviani, Karina (Cermin Dunia Kedokteran, 2025)
Teledermoscopy, as a component of telemedicine, represents an important innovation in dermatological healthcare that enhances accessibility, effectiveness, and the overall quality of medical services in Indonesia. This technology provides significant benefits, particularly for communities in regions with limited access to dermatology specialists. Law Number 17 of 2023 concerning Health and Government Regulation Number 28 of 2024 serve as the primary legal foundations supporting the implementation of teledermoscopy in Indonesia. These regulations address the legality of practice, patient data protection, information security standards, and the responsibilities of healthcare professionals and electronic system providers in delivering digital health services. Teledermoscopyenables remote examination, diagnosis, and monitoring of skin lesions through digital dermoscopy devices connected to the national health information system. The technology accelerates diagnosis, facilitates referrals, and broadens access to dermatological care. With a robust legal framework, continuous professional training, and reliable digital infrastructure, teledermoscopy has the potential to become a strategic component in the transformation of Indonesia’s national healthcare system.